Is 4-Hydroxynonenal a Predictive Parameter for the Development of Joint Erosion in Patients With Rheumatoid Arthritis? - Gürkan AKGÖL,; Hasan ULUSOY,; Selda TELO,; Arif GÜLKESEN,; Tülay YILDIRIM,; Ahmet Kürşad POYRAZ,; Arzu KAYA, (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate serum 4-hydroxynonenal (4-HNE) levels and its clinical and radiological significance in patients with rheumatoid arthritis (RA). Patients and methods: The study included 40 patients (8 males, 32 females; mean age 51.4±11.2 years; range 24 to 72 years) with RA and 30 healthy controls (8 males, 32 females; mean age 53.0±11.7 years; range 24 to 72 years. Serum 4-HNE levels were measured using sandwich enzyme-linked immunosorbent assay method. Patients with disease activity score 28 ≤3.2 and >3.2 were allocated into low and high/moderate disease activity groups, respectively. Additionally, patients were divided into two groups as early RA (disease duration ≤2 years) and established RA (disease duration ≥2 years). Functional disability was evaluated using health assessment questionnaire. Radiographs were scored using the modified Larsen scoring. Results: Serum 4-HNE levels in patients with RA were significantly higher than controls (p=0.001). Serum 4-HNE levels did not correlate with laboratory or clinical parameters of disease activity including erythrocyte sedimentation rate, C-reactive protein, disease activity score 28, and health assessment questionnaire. Serum 4-HNE levels were higher in patients with established RA than patients with early RA (r=0.487, p=0.001). Besides, modified Larsen score which indicates structural damage correlated significantly with serum 4-HNE levels (p=0.001). Conclusion: These results indicate that serum 4-HNE levels may be used as an indicator for structural damage such as erosions in the early stage of RA; however, they are not efficient to monitor disease activity.